The first report of prion protein gene sequences in Dybowski’s frog and the American bullfrog: high amyloid propensity of the frog prion protein - Won, Sae-Young; Kim, Yong-Chan (Frontiers in Animal Science, 2024)
Prion diseases are fatal infectious neurodegenerative diseases caused by the proteinase Ksensitive form of prion protein (PrP Sc ). The exact origin of prion seeding and the transition factor of PrP Sc has not been elucidated. The main hosts of prion diseases are herbivores, so the feces and corpses of Amphibians can seed PrP Sc through ecosystems. The frog is an excellent candidate for transmission studies for this reason, but genetic analyses of the prion protein gene (PRNP) in the context of prion-related characteristics of frog species are lacking.We amplified frog PRNP gene sequences in Dybowski's frog and the American bullfrog by polymerase chain reaction (PCR) and amplicon sequencing. In addition, we carried out multiple sequencing alignments and annotated major PrP components including signal peptide, tandem repeat domain, and PrP C -PrP Sc interaction region of frog PrPs by bioinformatics tools. We predicted secondary and tertiary structures and amyloid propensities of frog PrPs using AlphaFold2 and AMYCO, respectively. We obtained DNA sequences of the PRNP gene in Dybowski's frog and the American bullfrog, as well as a partially conserved palindromic sequence (PrP C -PrP Sc interaction region) and absence of tandem repeat region of PrP in seven frog species. We analyzed protein structure of among these frog species and found that the high Himalaya frog has high aggregation propensity and the western clawed frog does not have the N-terminal signal peptide. To the best of our knowledge, this was the first comparative genetic study regarding prion-related features of frog species.